种夹套芯棒热轧制大口径钛及钛合金薄壁无缝管的方法 (2019)
本发明公开了种夹套芯棒热轧制钛及钛合金薄壁无缝管的方法，该方法用真空自耗电弧炉二次熔炼成铸锭；将铸锭经二火次锻造成棒材；再扒皮加工；然后用三辊(或两辊)斜轧穿孔制成无缝管坯；经夹套芯棒热轧制直接获得成品薄壁无缝管；对于有特殊性能要求的管材，将喷砂、酸洗、抛磨等加工后的管坯进行进步冷轧等深加工，得到性能更为优越的成品管材，然后对管材酸洗处理得到大口径薄壁无缝管；最后将成品管材进行真空退火处理及修磨定尺包装。采用本发明方法制造的大口径薄壁钛及其合金无缝管力学性能优异，主要用于石油、化工、海洋等行业的压力容器、工业管道、冷凝器、钻井等领域，满足防腐管材的需求。 The invention discloses a method for hot rolling of a large-opening-diameter titanium and titanium alloy thin-wall seamless pipe through a jacket core bar. According to the method, a vacuum self-consuming arc furnace is used for secondary smelting to form a casting ingot; the casting ingot is subject to two-heating-number forging to form the bar; scaling machining is carried out; three-roller (or two-roller) skew rolling punching is used for making a seamless pipe blank; for pipe materials with the special property needs, the pipe blank subject to sand blasting, acid pickling, polishing and grinding and the like is subject to further cold rolling and other deep machining, a finished product pipe with the more excellent property is ob